Analisis Kebutuhan Pengembangan E-Modul Bermuatan Video Pembelajaran pada Pendidikan Jarak Jauh bagi Calon Guru Fisika - Anggreini Anggreini; Dimas Permadi (JURNAL EKSAKTA PENDIDIKAN (JEP), 2021)
Distance Education (PJJ) as a learning solution during the COVID-19 pandemic at the University of Lampung has not been implemented optimally. The purpose of this study was to find out the circumstances and needs of prospective physics teacher students while carrying out PJJ online from their respective homes. As well as analyzing the materials and assignments to achieve the Subject Learning Outcomes (CPMK) of Educational Research Statistics. This study uses a descriptive analysis method with a research instrument in the form of a questionnaire distributed online with the help of a google form. The sample in this study was 53 students of physics teacher candidates in the Physics Education Study Program, University of Lampung. The results of this study indicate that the condition of students in implementing PJJ is that they already have adequate facilities both from electricity infrastructure, internet networks, devices, and getting support from family. However, students find it difficult to understand practical learning when using media and learning methods that are not varied. The analysis of materials and tasks developed from CPMK Educational Research Statistics consists of three main materials with ten learning videos, and each student is asked to complete matters an educational research case using SPSS. Based on the results of this needs analysis, lecturers need to develop a teaching material, namely an e-module containing learning videos that can facilitate prospective physics teacher students in implementing PJJ.